Quantifying Protein and Nitrogen Levels in Paramphistomum species - Gupta, Sheela (Journal for Research in Applied Sciences and Biotechnology, 2023)
Quantifying protein and nitrogen levels in Paramphistomum species is crucial for understanding their biochemical composition and metabolic processes. This study aimed to assess the total protein and nitrogen content in Paramphistomum spp. employing established assay techniques. The Folin phenol method, a widely recognized approach for protein estimation, and Varley's method for nitrogen determination were utilized. Our findings revealed that Paramphistomum spp. contained approximately 49.18% total protein and 3.57% total nitrogen by dry weight. These results underscore the applicability of traditional assay methods in elucidating the biochemical profiles of helminth parasites, offering valuable data for further research on their physiological characteristics and nutritional requirements.